Extrauterine leiomyomas in uncommon locations: two case reports and literature review - Yavuz, Onur; Kula, Ali Hakan; Bayramoğlu, Zeynep; Aydin, Nur Yağ mur; Mankan, Kadir Alper; Akdöner, Aslı (Frontiers in Medicine, 2024)
Objectives: This study aims to provide an overview of the diagnosis, treatment, and follow-up management of vulvar and vaginal leiomyomas through the presentation of two rare cases. Methods: Detailed clinical presentations, surgical procedures, histopathological examinations, and follow-up outcomes of two cases of vulvar and vaginal leiomyomas are described. Relevant literature is also reviewed to contextualize the findings. Results: Both patients underwent successful surgical excision of the leiomyomas with no perioperative or postoperative complications. Histopathological examinations confirmed the diagnosis of leiomyoma based on characteristic microscopic features and immunohistochemical analyses. Conclusion: Vulvar and vaginal leiomyomas are rare benign tumors that require careful evaluation for accurate diagnosis and appropriate management. Surgical excision remains the primary treatment modality, and long-term follow-up is essential for monitoring recurrence and ensuring favorable outcomes.